Perlindungan Hukum pada Tradisi Menugal sebagai Kearifan Lokal di Kecamatan Arut Utara - Wahyu Purwaningsih; Fira Wulansari (Mathematics Education Study Program, 2023)
The tradition of cutting off is one of the local wisdom that still exists carried out by the people of North Arut District, West Kotawaringin Regency. This tradition is carried out at the time of the start of the growing season around October to December by performing certain rituals by burning the land to be planted. Law number 32 of 2009 is explained on the protection of local wisdom of indigenous peoples and Central Kalimantan Regional Regulation Number 1 of 2020 concerning Forest and Land control provides protection and mechanisms for burning forests and land. The obstacle faced in legal protection in this tradition is that the local government only provides appeals through brochures and billboards and there is less socialization and understanding to the people who carry out this tradition so that the provisions in the legislation are acceptable and do not give fear about legal threats.